Diversity within the adenovirus fiber knob hypervariable loops influences primary receptor interactions - Alexander T. Baker (Nature Portfolio, 2019)
Adenovirus based (AdV) vectors are promising platforms for therapeutics and vaccines, but receptor usage of serotypes in clinical development remains unclear. Here, based on crystal structures and modeling, Baker et al. show that HAdV-D26/48 fiber knob protein interacts weakly with CAR but not with CD46 or DSG2.